Building a digital learning space culture in elementary school - Wahidmurni, Wahidmurni; Firdiansyah, Yhadi; Lestantyo, Prayudi; Susilawati, Samsul; Mubarok, Harir; Cahyono, M. Dwi (Edelweiss Applied Science and Technology, 2025)
The study aims to investigate the grand design and strategy for building a digital learning space culture, including its impact on learning in elementary schools. Data were gathered by conducting interviews with academics, observing learning processes, and reviewing school records. Throughout the data collection process, data were evaluated using data presentation, data condensation patterns, and conclusion drawing. The study’s conclusions were validated using triangulation and data collection methodologies. The study’s findings revealed that (1) the grand plan for creating a digital culture was not fully developed, and the provision of digital facilities was tailored to fit limited needs and budgets; (2) the principal implemented a strategy for creating a digital culture for teachers by providing digital facilities and infrastructure, establishing an IT team, and providing professional teacher training; the interaction of the three supported digital culture; and (3) the positive impacts included more engaging learning, increased teacher administration efficiency, and improved students’ and instructors’ technology skills, whereas the negative effects included a loss in students’ fine motor skills and social competence. The implication is that a thorough investigation is required to determine the best formula for employing digital media in learning so that learning effectiveness can be maximized.